Rockfish abundance, recruitment, and community structure trends in the western Strait of Juan de Fuca, Washington, 2005-2023 - Shawn E. Larson; Katie Shelledy; Daniela Escontrela Dieguez; Jeff Christiansen; Amy Y. Olsen; Zachary Randell; Megan H. Williams; Chris VanDamme; Dayv Lowry; William Jasper (Frontiers in Marine Science)
Rockfish, Sebastes spp., are bottomfish that come in a variety of shapes, sizes and colors with 28 species recognized in the Salish Sea. Based on increasing concern over the long-term stability of rockfish populations in Washington by state and federal agencies, the Seattle Aquarium formalized a benthic monitoring program starting in 2005 on rocky reefs west and east of Neah Bay, Washington. Diver-operated video (DOV) surveys were conducted annually to quantify patterns in bottomfish (rockfish and other species associated with rocky reefs) abundance and stability over time. Divers performed 100-meter video transects devised to be both non-invasive and repeatable, for assessing both relatively sessile bottomfish and for schooling, transitory rockfish species. Strip transects were conducted annually in August from 2005 through 2023 at five permanently marked index sites. Species-specific relative abundance data for bottomfish were later extracted by biologists from archived video. Notably, over the 19-year study period, bottomfish abundance was stable or increased at all sites, driven by significant increases in eight rockfish species: Black/Deacon, Canary, China, Copper, Quillback, Tiger, and Yellowtail. Relatively few Puget Sound, Vermillion, Widow, and Yelloweye Rockfish individuals were documented, and their abundance did not increase throughout the study. Boccaccio where never encountered during the 19 year monitoring period. All sites displayed relative stability in fish community structure over time. We documented low levels of young-of-the-year (YOY) rockfish recruitment over the years with one major recruitment event in 2016. Despite an increase in abundance across eight rockfish species, recruitment events remained infrequent. Furthermore, Boccaccio and Yelloweye rockfish, both protected species, were either never or rarely encountered, respectively, underscoring the need for sustained conservation efforts and expanded long-term monitoring for species with long generation times such as rockfish.